A Critical Examination of Operational Management Practices at PT Calvary Abadi Mojokerto - Muttaqin, Muh. Syaukin; Syahbudi, Muhammad (Majapahit Journal of Islamic Finance and Management, 2023)
The implementation of operational management in a corporation is of utmost importance. Irrespective of the diverse operational processes that are present inside the organization. There is a potential for the existence of conditions and restrictions. The objective of this study is to examine the application of operational management practices within local enterprises in Mojokerto City, specifically focusing on PT Nasional Industry Gasses Indonesia. The research findings indicate that PT Calvary Abadi has implemented many operational management strategies, one of which is quality management through the adoption of ISO standards as a mandatory operational requirement. The study's findings highlight the effective approach of PT Calvary Abadi in ensuring quality, planning, and collaboration within the organization through the implementation of operational management strategies such as ISO standard adoption, annual forecasting, and supply chain coordination. The organization maintains annual management forecasting phases and establishes a well-defined supply chain management structure that facilitates coordination between the company, its suppliers, and consumers. The ideal geographical plan for the company has been determined. This study utilizes qualitative data acquired through the implementation of HR/HSE interview procedures throughout several companies. The research did not employ any sample methodology and solely focused on PT Calvary Abadi as the subject of analysis for operational management.